DC Subsets Regulate Humoral Immune Responses by Supporting the Differentiation of Distinct Tfh Cells - Bouteau, Aurélie; Kervevan, Jérôme; Su, Qingtai; Zurawski, Sandra M.; Contreras, Vanessa; Dereuddre-Bosquet, Nathalie; Le Grand, Roger; Zurawski, Gerard; Cardinaud, Sylvain; Levy, Yves; Igyártó, Botond Z. (Frontiers in Immunology, 2019)
To determine the contribution of skin DC subsets in the regulation of humoral immunity, we used a well-characterized antigen targeting system to limit antigen availability and presentation to certain skin-derived DC subsets. Here we show that delivery of foreign antigen to steady state Langerhans cells (LCs) and cDC1s through the same receptor (Langerin) led to, respectively, robust versus minimal-to-null humoral immune response. LCs, unlike cDC1s, supported the formation of germinal center T follicular helper cells (GC-Tfh) antigen dose-dependently and then, likely licensed by these T cells, some of the LCs migrated to the B cell area to initiate B cell responses. Furthermore, we found that the cDC1s, probably through their superior T cell activation capacity, prevented the LCs from inducing GC-Tfh cells and humoral immune responses. We further show that targeted delivery of cytokines to DCs can be used to modulate DC-induced humoral immune responses, which has important therapeutic potential. Finally, we show that human LCs, unlike monocyte-derived DCs, can support GC Tfh generation in an in vitro autologous system; and in agreement with mouse data, we provide evidence in NHP studies that targeting LCs without adjuvants is an effective way to induce antibody responses, but does not trigger CD8+ T cell responses.